Polis and personification in classical Athenian art - Smith, Amy Claire, 1966- (Monumenta Graeca et Romana, 2011)
In this study Dr Smith investigates the use of political personifications in the visual arts of Athens in the Classical period (480-323 BCE). Whether on objects that served primarily private roles (e.g. decorated vases) or public roles (e.g. cult statues and document stelai), these personifications represented aspects of the state of Athens-its people, government, and events-as well as the virtues (e.g. Nemesis, Peitho or Persuasion, and Eirene or Peace) that underpinned it. Athenians used the same figural language to represent other places and their peoples. This is the only study that uses personifications as a lens through which to view the intellectual and political climate of Athens in the Classical period.